PENGARUH GREEN MARKETING DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN DI BUSINESS CENTER ALAMANDA DELTA SURYA - Putri Farikh Rizka; Ragil Satria; Laily Muzdalifah (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
This study aims to analyze the effect of green marketing and brand image on the purchasing decisions of tupperware consumers at the Alamanda Delta Surya Business Center. The population in this study were all Tupperware consumers aged 17-58 years. The sampling technique used purposive sampling by taking 100 respondents. Data collection through distributing questionnaires. The data analysis method uses Multiple Linear Regression through the SPSS application version 21 for Windows. The results of the study show that partially Green Marketing has a positive and significant effect on Tupperware Purchasing Decisions, Brand Image has a positive and significant effect on Tupperware Purchase Decisions and simultaneously Green Marketing and Brand Image have a significant effect on Purchasing Decisions at the Alamanda Delta Surya Business Center.